Backstepping Control for Induction Motors with Input and Output Constrains - Nguyen, T. L.; Vo, T. H.; Le, N. D. (Engineering, Technology & Applied Science Research, 2020)
In practice, the applied control voltage for an induction motor drive system fed by a voltage source inverter has a limit depending on the DC bus capacity. In certain operations such as accelerating, the motor might require an excessively high voltage value that the DC bus cannot supply. This paper presents a control solution for the bounded control input problem of the induction motor system by flexibly combining a hyperbolic tangent function in a backstepping control design procedure. In addition, the barrier Lyapunov function is also employed to force speed tracking error in a defined value. The closed-loop system stability is proven, and the proposed control is verified through numerical simulations.